Perceptual distortions characteristic of Alice in Wonderland syndrome in contemporary figurative painting - Hyatt, Erica; Blom, Jan Dirk (Frontiers in Psychiatry, 2024)
BackgroundAlice in Wonderland syndrome (AIWS) is a neurological condition characterized by perceptual distortions, most of which are visual in nature (metamorphopsias). Over the past decade there has been a movement in contemporary figurative painting away from strict mimesis toward depicting distortions of the painting’s subject, called disrupted realism. In certain cases the similarities between the distortions in those paintings and those characteristic of AIWS are so striking that we suspect that artists may have experienced distorted perceptions themselves and used them for creative inspiration.MethodsTo empirically test this hypothesis we interviewed 20 painters who frequently use distortions in their work, using the SIntAD, a tailor-made, semi-structured questionnaire. We then carried out a phenomenological analysis of the perceptual phenomena reported on, and compared them with those in their paintings.ResultsOf the artists interviewed, 85% reported on having experienced positive disorders of perception in general (comprising hallucinations, perceptual distortions and other perceptual phenomena), with 55% reporting on a total number of 15 metamorphopsias. Most artists had not been aware of having these distortions to their perception. Nonetheless, most did not use these specific distortions in their work, but rather different types.ConclusionSymptoms of AIWS and other positive disorders of perception are common among contemporary painters who frequently use distortions in their figurative work, although perhaps not more common than in the general population. Artists in the disrupted-realism movement tend not to mimic their own perceptual distortions in their work, although they do feel inspired to distort their work in different ways.